Target identification reveals protein arginine methyltransferase 1 is a potential target of phenyl vinyl sulfone and its derivatives. Issue 2 (20th April 2018) - Yu, Cheng-Han; Chou, Chi-Chi; Lee, Der-Yen; Khoo, Kay-Hooi; Chang, Geen-Dong
Abstract : Phenyl vinyl sulfone (PVS) and phenyl vinyl sulfonate (PVSN) inactivate protein tyrosine phosphatases (PTPs) by mimicking the phosphotyrosine structure and providing a Michael addition acceptor for the active-site cysteine residue of PTPs, thus forming covalent adducts between PVS (or PVSN) and PTPs. We developed a specific antiserum against PVS. This antiserum can be used in general antibody-based assays such as immunoblotting, immunofluorescence staining, and immunoprecipitation. Target identification through immunoprecipitation and mass spectrometry analysis reveals potential targets of PVS, mostly proteins with reactive cysteine residues or low-p K a cysteine residues that are prone to reversible redox modifications. Target identification of PVSN has been conducted because the anti-PVS antiserum can also recognize PVSN. Among the targets, protein arginine methyltransferase 1 (PRMT1), inosine-5′-monophosphate dehydrogenase 1, vimentin, and glutathione reductase (GR) were further confirmed by immunoprecipitation followed by immunoblotting. In addition, PVSN and Bay11-7082 inhibited GR activity, and PVS, PVSN, and Bay 11-7082 inhibited PRMT1 activity in in vitro assays. In addition, treatment of PVSN, Bay11-7082, or Bay 11-7085 in cultured HeLa cells can cause the quick decline in the levels of protein asymmetric dimethylarginine. These results indicate that the similar moiety among PVS, PVSN, Bay 11-7082, and Bay 11-7085 can be the key structure of lead compounds of PRMT1. Therefore, we expect to use this approach in the identification of potential targets of other covalent drugs.